Habinek, T. (2005) The World of Roman Song. From Ritualized Speech to Social Order - Soledad Correa (Anales de Filología Clásica, 1970)
Reseña de HABINEK, T. (2005) The World of Roman Song. From Ritualized Speech to Social Order. Baltimore: John Hopkins University Press, 329 pp. ISBN: 0‐8018‐8105‐6.